2021
DOI: 10.1177/23333936211028176
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Impact of Technology-Facilitated Abuse and Its Relationship with Domestic Violence: A Qualitative Study on Experts’ Perceptions

Abstract: Technology-facilitated abuse can be a serious form of domestic violence. Little is known about the relationship between technology-facilitated abuse and other types of domestic violence, or the impact technology-facilitated abuse has on survivors. The aim of this interpretative descriptive study is to understand domestic violence specialist service providers’ perspectives on the impact of technology-facilitated abuse, and the link between technology-facilitated abuse and other forms of domestic violence. A qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 42 publications
3
8
0
Order By: Relevance
“…Our study also revealed new perpetrator narratives about the TAR behaviours undertaken and how different technologies are utilised to engage in TAR. These motive, behavioural and technology-oriented findings are being reported elsewhere across two other manuscripts (Fiolet et al. , 2023; McKay et al.…”
Section: Effectiveness Of Story Completion In Exploring Tar Perpetrationsupporting
confidence: 76%
See 1 more Smart Citation
“…Our study also revealed new perpetrator narratives about the TAR behaviours undertaken and how different technologies are utilised to engage in TAR. These motive, behavioural and technology-oriented findings are being reported elsewhere across two other manuscripts (Fiolet et al. , 2023; McKay et al.…”
Section: Effectiveness Of Story Completion In Exploring Tar Perpetrationsupporting
confidence: 76%
“…A further example relates to cultures in which a TAR perpetrator’s sharing of nude or sexual images of his or her female partner could have devastating social or even fatal consequences for the female partner because of the shame it brings about for the family (The eSafety Commissioner, 2019; Brown et al. , 2021b; Fiolet et al. , 2021).…”
Section: Effectiveness Of Story Completion In Exploring Tar Perpetrationmentioning
confidence: 99%
“…Their findings showed that TFA escalated post-separation. Fiolet et al (2021) interviewed 15 domestic violence experts about their perceptions of TFA and IPV and obtained similar findings to those of prior studies (e.g., Dragiewicz et al, 2021;Flynn et al, 2021). That is, TFA was found to be a form of control and an extension of IPV.…”
Section: Studies Of Tfa In the Context Of Ipvsupporting
confidence: 70%
“…We identified a growing research trend in three areas: “coercive control,” “technology,” and “pandemic,” all of which gave a solid avenue for strengthening further research. Digital technology was identified as a new “vehicle” of “weapon” for expanding and magnifying the classic ills of FADV, jeopardizing the progress accomplished by advocates over the last 30 years (Drouin et al, 2015; Fiolet et al, 2021; Woodlock et al, 2020). Despite the rise of this cutting-edge topic in current articles, the existing literature focused on the understanding of the nature and scope of technology-facilitated violence, as well as the response to it.…”
Section: Discussionmentioning
confidence: 99%